Latent Cytomegalovirus Infection and Previous Capsular Polysaccharide Vaccination Predict Poor Vaccine Responses in Older Adults, Independent of Chronic Kidney Disease. (16th March 2021) - Wall, Nadezhda; Godlee, Alexandra; Geh, Daniel; Jones, Charlotte; Faustini, Sian; Harvey, Ruth; Penn, Rebecca; Chanouzas, Dimitrios; Nightingale, Peter; O'Shea, Matthew; Richter, Alex; Moss, Paul; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) are more prone to severe infection. Vaccination is a key strategy to reduce this risk. Some studies suggest vaccine efficacy may be reduced in patients with CKD, despite preserved maintenance of long-term responses to some pathogens and vaccines. Here, we investigated immune responses to 2 vaccines in patients with CKD to identify predictors of immunological responsiveness. Methods: Individuals >65 years old, with or without nondialysis CKD (n = 36 and 29, respectively), were vaccinated with a nonadjuvanted seasonal influenza vaccine (T-dependent) and Pneumovax23 (23-valent pneumococcal polysaccharide [PPV23], T-independent). Humoral responses were measured at baseline, day 28, and 6 months. Lymphocyte subset and plasma cell/blast analyses were performed using flow cytometry. Cytomegalovirus (CMV) serotyping was assessed by enzyme-linked immunosorbent assay. Results: Only modest responsiveness was observed to both vaccines, independent of CKD status (25% adequate response in controls vs. 12%–18% in the CKD group). Unexpectedly, previous immunization with PPV23 (median 10-year interval) and CMV seropositivity were associated with poor PPV23 responsiveness in both study groups ( P < .001 and .003, respectively; multivariable linear regression model). Patients with CKD displayed expanded circulating populations of T helper 2 and regulatory T cells, which were unrelated to vaccine responses. Despite fewer circulating B cells, patients with CKD were able to mount a similar day 7 plasma cell/blast response to controls. Conclusion: Patients with nondialysis CKD can respond similarly to vaccines as age- and sex-matched healthy individuals. CKD patients display an immune signature that is independent of vaccine responsiveness. Prior PPV23 immunization and CMV infection may influence responsiveness to vaccination. Clinical Trials Registration . NCT02535052 Abstract : Patients with nondialysis Chronic Kidney Disease (CKD) can mount similar responses to vaccination as controls. Subtle changes in lymphocyte phenotype are seen in CKD when controlled for effect of Cytomegalovirus (CMV). Latent CMV infection and previous PPV23 vaccination are associated with poorer vaccine responses.